Comprehensive Appraisal of Magnetic Resonance Imaging Findings in Sustained Rheumatoid Arthritis Remission: A Substudy. Issue 7 (July 2015) - Ranganath, Veena K.; Motamedi, Kambiz; Haavardsholm, Espen A.; Maranian, Paul; Elashoff, David; McQueen, Fiona; Duffy, Erin L.; Bathon, Joan M.; Curtis, Jeffrey R.; Chen, Weiling; Moreland, Larry; Louie, James; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the effect of sustained American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) Boolean remission on residual joint inflammation assessed by magnetic resonance imaging (MRI) and to secondarily evaluate other clinical definitions of remission, within an early seropositive rheumatoid arthritis (RA) cohort. Methods A subcohort of 118 RA patients was enrolled from patients who completed the 2‐year, double‐blind randomized Treatment of Early Aggressive Rheumatoid Arthritis (TEAR) trial. Patients received a single contrast‐enhanced 1.5T MRI of their most involved wrist. Two readers scored MRIs for synovitis, osteitis, tenosynovitis, and erosions. Clinical assessments were performed every 3 months during the trial and at time of MRI. Results The subcohort was 92% seropositive with mean age 51 years, duration 4.1 months, and Disease Activity Score in 28 joints using the erythrocyte sedimentation rate 5.8 at TEAR entry. Total MRI inflammatory scores (tenosynovitis + synovitis + osteitis) were lower among patients in clinical remission. Lower MRI scores were correlated with longer duration of Clinical Disease Activity Index (CDAI) remission (ρ = 0.22, P = 0.03). At the time of MRI, 89 patients had no wrist pain/tenderness/swelling; however, all 118 patients had MRI evidence of residual joint inflammation after 2 years. No statistically significant differences in damage or MRI inflammatory scores were observed across treatment groups. Conclusion This is the first detailed appraisal describing the relationship between clinical remission cut points and MRI inflammatory scores within an RA randomized controlled trial. The most stringent remission criteria (2011 ACR/EULAR and CDAI) best differentiate the total MRI inflammatory scores. These results document that 2 years of triple therapy or tumor necrosis factor plus methotrexate treatment in early RA does not eliminate MRI evidence of joint inflammation.